Mothering, Running, and the Renegotiation of Running Identity: Graduate Student Spotlight - Skinner, Samantha (Qualitative Sociology Review, 2015)
Qualitative interviews with six female runners shed light on the gender gap in women’s participation in shorter versus longer road races. The interviews reveal that “mother guilt” and “time constraints” play a significant role in the development of a running identity among women. While the running community promotes a discourse centered around a “disembodied” runner — someone totally and unconstrainedly dedicated to running — the participants in this study experienced conflicts between their roles as mothers and their identity as runners. The conflicts led them to engage in challenging the dominant discourse by actively negotiating a mothering and running identity. The findings suggest that women are redefining the boundaries around running and subsequently — running subculture itself.